Job Status and Depressive Symptoms in Older Employees: An Empirical Analysis with Share Data - Moreno Mencia, Patricia; Cantarero Prieto, David (European Journal of Mental Health, 2020)
Background: Depression is a frequently occurring mental illness that has been shown to be strongly related to important life outcomes, such as education or labor. Few studies focus on the impact of job status on the risk of depressive symptoms. Aims: We used longitudinal data from the Survey of Health, Ageing and Retirement in Europe for people aged from 50 to 64 years old across 11 countries to analyze how the type of job is related to depression. Methods: Associations between the type of job and depressive symptoms are analyzed using logistic multilevel models. Results: The risk of depressive symptoms is higher for self-employers. Among the self-employed, women are more at risk (OR: 3.22) as well as those who visit the doctor more frequently. On the other hand, people reporting a good quality of life and those living with a partner demonstrate a lower risk of depressive symptoms. These effects manifest less for employees, while the risk is also higher for women and those visiting the doctor frequently but lower for those who have a good quality of life or children. Conclusions: The stress suffered at work is related to a higher risk of depressive symptoms. The self-employed usually experience more stress at work, as this is related to a larger responsibility and, usually, less stability.